HUBUNGAN ANTARA TINGKAT KECEMASAN DENGANSTRATEGI KOPINGPASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS - Desti ' Sasmita; Bayhakki ' '; Oswati ' Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The research aimed to determine therelationship between ofanxiety andcopingstrategiesin patients undergoinghemodialysistherapyat ArifinAhmad General Hospital. This researchwas description correlation with cross sectional approach. Sampling techniquein this research was simple randomsamplingwith30respondents. Instruments usedwerequestionnaires which weretested the validityandreliability. Data analysis usedunivariateandbivariateanalysis. The result showed that pvalue= 1,0, it could be concluded that there was no relationship between anxiety leveland coping strategy of chronic renal failure in patients undergoinghemodialysisat ArifinAhmad General Hospital.Based on the result,suggested tohealth workers who directlyengagedin the service ofHemodialysis to make effortspromotion and preventionof anxiety with regular program throughhealth educationaboutanxiety management. Keywords : Anxiety, coping strategy, hemodialysis